PENGABDIAN MASYARAKAT MELALUI PROGRAM KULIAH KERJA LAPANGAN (KKL) DI DESA MARTADINATA KECAMATAN TELUK PANDAN - Rahmi, Aulia Nur; Pebriyanti, Pebriyanti; Munfiatik, Siti; Baso, Sholikah Sukma; Pratama, Zikri; Velyna, Tri (P3M STAI Sangatta, 2024)
Field Work Lectures (KKL) is one form of application of the Tri Dharma of higher education. The aim of this activity is to provide an understanding of the importance of education for early childhood and society in general. The method used in this service is Participatory Action Research (PAR). The results of KKL activities are that they have a positive impact on both students and students at SDN 006 Martadinata, TK Marta Jaya and TPQ RT 08, RT 01, and RT 14. There are several series of activities, namely teaching, religious education, socializing the benefits of saving, distributing basic necessities, to making village profile videos. With this activity, it is hoped that students can understand the importance of education and the importance of saving from an early age. Religious teaching activities are also expected to provide students with an understanding of how to read the Al-Qur'an properly and correctly according to the rules of tajwid and makhorijul letters.